Regarder l’immense - Marcia Sá Cavalcante Schuback (Projets de Paysage)
The text presents elements for a phenomenology of landscape departing from a reflexive description of Rembrandts’ landscapes. Following up how Rembrandt depicts backgrounds as landscapes and landscapes as the event of seeing, the text proposes to think of landscape as a looking into immensity and as the immensity of the regard. It aims to show how Rembrandt’s landscapes set on the canvas the instant when the infinitely small touches the infinitely big, clarity and obscurity coincide, sky and earth become undifferentiated, the visible meets the invisible, the human and the non-human discover each other one inside the other and thereby as a non-other.